SELF-ASSESSMENT OF PRIMARY CARE NURSES ABOUT CARE FOR PEOPLE WITH VENOUS ULCERS: A CROSS-CUTTING STUDY (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To identify the self-knowledge of primary care nurses about care for people with venous ulcers. Method: This is a cross-sectional study with 40 nurses working in health units. Two data collection instruments were used: characterization, developed by the author, and self-assessment on venous ulcers. Results: All questions of the self-assessment instrument reached medians classified as little level of knowledge, except questions related to the application of elastic compression therapy, with the median = 3 (moderate), and the evaluation of lower limbs to investigate arterial involvement, with 3.50, between little and moderate. The item cleaning the lesion stood out, which obtained median = 4 (little) and the highest average found in the  responses, 4.03 (little). Conclusion:The nurse’s self-assessment reached moderate and low scores of clinical practice in terms of knowing (theoretical knowledge) and doing (practical knowledge) in the care of people with venous ulcers. Venous ulcer is a complex wound and requires knowledge from nurses about the pathophysiology and appropriate treatment, interfering with the improvement of the person’s quality of life. It is believed that this study can encourage the reflection of this professional and education actions in the services.